Pelatihan Administrasi Pelaporan Bandes Bagi Pegawai Desa Karanganyar Kabupaten Pesawaran - Hendri , Hendri; Syarif, Arman (Jurnal Pemberdayaan Ekonomi, 2025)
Purpose: This study aims to improve the understanding and skills of village officials in systematically preparing administrative reports on village fund allocations (Bandes) through a participatory training program held in Karanganyar Village, Pesawaran Regency. Methodology/approach: This study employed a qualitative descriptive approach with educational-participatory methods. The one-day training included administrative theory, interactive discussions, and practical report writing. Participants were village officials and staff, with data collected through observation, documentation, and post-training evaluation. Results/findings: The training results showed a significant improvement in participants’ understanding of administrative principles and their ability to prepare Bandes reports. There was a notable increase in the accuracy and completeness of the reports produced during the practical session. Participants also demonstrated high enthusiasm during discussions, indicating the relevance and necessity of such training for improving village governance performance. Conclutions: This training effectively equipped village officials with essential administrative skills for managing village funds. The activity also demonstrated that participatory training approaches can successfully bridge the gap between administrative theory and practical implementation in local governance. Limitations: This study contributes to capacity-building efforts for village apparatuses and promotes transparent and accountable village governance. The training model can be replicated in other villages with similar administrative development needs. Contribution: The limitation of this study lies in the narrow scope of participants, which was limited to a single village, and the short duration of the training, which did not allow for long-term evaluation of its impact on field implementation.